Ramona the pest - Cleary, Beverly; Dockray, Tracy (New York : HarperTrophy, 2006)
Ramona starts kindergarten where her good intentions and uncontrollable curiosity lead her to be labeled a pest.
Book Links (A.L.A.).
Child Study Children's Book Committee.
Wilson's Children.
5.5.
5.5
3-6
Keywords: Kindergarten -- Juvenile fiction; Quimby, Ramona (Fictitious character) -- Juvenile fiction; Schools -- Juvenile fiction; Kindergarten -- Fiction; Quimby, Ramona (Fictitious character) -- Fiction; Schools -- Fiction; Kindergarten -- Fiction; Quimby, Ramona (Fictional character) -- Fiction; School stories